Relationship between dynamic capability view and organizational resilience: Findings from a symmetric approach - Ali Shojaee; Laszlo Vasa (Problems and Perspectives in Management, 2024)
The COVID-19 outbreak has underscored the importance of strengthening an organization’s resilience and adaptive capability. In emerging and uncertain conditions, firms must adopt new capabilities to develop and survive unstable and unforeseen crises. The purpose of this study is to examine the difference between organizational resilience and the antecedents that are validated using a quantitative survey. The respondents consist of 157 top employees from 21 private service firms at the managerial level in Bangladesh. The proposed relationship is measured using the partial least squares structural equation modeling (PLS-SEM), a symmetric approach, using SmartPLS 4 software. The findings help to produce the path coefficient with organizational resilience that can lead to sustainable environments in highly turbulent conditions. The PLS-SEM analysis indicates that the antecedents of flexibility, agility, and redundancy have a strong and meaningful association with organizational resilience in response to disruptions. Therefore, this paper shows evidence that the measurement scales more effectively account for uncertainty in achieving resilience, supporting the role of the dynamic capability view.